The Relationship Between Hypertension and Blood Glucose Levels Among Police Officers Aged 30–60 Years at the Pasuruan Police Resort - Herdiana, Rency Angelika; Sunaryati, Titiek (Jurnal EduHealth, 2025)
Hypertension and elevated blood glucose levels are two chronic conditions that are often found concurrently and are major risk factors for cardiovascular disease. Although the relationship between the two has been extensively studied, specific data within certain professional groups such as police officers remain limited. This study aimed to examine the relationship between hypertension and blood glucose levels among police officers aged 30–60 years at the Pasuruan Police Resort. The study employed a cross-sectional design with a quantitative approach. The sample consisted of 60 police officers selected using purposive sampling. Data were obtained through blood pressure measurements and random blood glucose tests, and then analyzed using the Chi-Square test and Fisher’s Exact Test. The results showed that 83.3% of respondents had hypertension, and 13.3% of them had elevated blood glucose levels. Statistical analysis using Fisher’s Exact Test revealed no significant relationship between hypertension and blood glucose levels (p = 0.330). It can therefore be concluded that there is no significant association between hypertension and blood glucose levels among police officers aged 30–60 years at the Pasuruan Police Resort. Further research is needed, taking into account other risk factors such as dietary patterns, physical activity, and family medical history.